2005
DOI: 10.4315/0362-028x-68.4.855
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Listeria monocytogenes Inoculated onto the Surface of Model Turkey Frankfurter Pieces Treated with Zein Coatings Containing Nisin, Sodium Diacetate, and Sodium Lactate at 4°C

Abstract: The antimicrobial effects of zein coatings containing nisin, sodium lactate, and sodium diacetate against Listeria monocytogenes on turkey frankfurters at 4 degrees C were determined. Our objectives were to determine whether zein, nisin, lactate, and diacetate alone or in combination could control the growth of L. monocytogenes on full-fat turkey frankfurters at 4 degrees C and to determine whether lactate or diacetate had any synergistic effect on the activity of nisin. Turkey frankfurter pieces surface inocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(25 citation statements)
references
References 22 publications
2
23
0
Order By: Relevance
“…The obtained results revealed that the zein-based film have no antibacterial activity against these bacterial strains. These results are in agreement with previous works of Janes and his colleagues (2002) and Lungu and Johnson (2005), as they showed that zein films had no effect on suppressing the growth of L. monocytogenes. Whereas, Schiff bases films exhibited higher antibacterial effect on the tested strains comparing with zein film.…”
Section: Antibacterial Activitysupporting
confidence: 94%
“…The obtained results revealed that the zein-based film have no antibacterial activity against these bacterial strains. These results are in agreement with previous works of Janes and his colleagues (2002) and Lungu and Johnson (2005), as they showed that zein films had no effect on suppressing the growth of L. monocytogenes. Whereas, Schiff bases films exhibited higher antibacterial effect on the tested strains comparing with zein film.…”
Section: Antibacterial Activitysupporting
confidence: 94%
“…Naturally sourced materials such as starch are an alternative for use as films or coverings for fruits (Pan, Chen, & Lai, 2013) and vegetables (Das, Dutta, & Mahanta, 2013). For meat products, several different biodegradable materials have been proposed as coatings including polysaccharides such as chitosan (Kanatt, Rao, Chawla, & Sharma, 2013), cellulose (Luchansky & Call, 2004), carrageenans (Martins et al, 2012), alginate (Juck, Neetoo, & Chen, 2010), pectins (Kang et al, 2007) and their various formulations (Bierhalz, Da Silva, & Kieckbusch, 2012) as well as proteins including gelatin, corn proteins and collagen (Lungu & Johnson, 2005). One potential source of food packaging and coatings that has been less studied is film from starches.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of either bacteriocins or bacteriocin-producing strains to restrict the growth of pathogenic bacteria such as Listeria monocytogenes in various food products is well described. The majority of the investigations are carried out on ready-to-eat foods including cheese (16) and meat products (17,19); however, fish (23) and vegetables (1) can also be preserved by bioprotection.…”
mentioning
confidence: 99%